FIRST DATA ON THE SPONGE FAUNA OF A SEMI-SUBMERGED CAVE OF THE ADRIATIC APULIAN COAST (SOUTHERN ITALY, MEDITERRANEAN SEA) - Schiavo, Antonella; Gimenez, Guadalupe; Oddenino, Muriel; Longo, Caterina (Biologia Marina Mediterranea, 2024)
Marine caves are vulnerable habitats considered an important hotspot for biodiversity in the Mediterranean Sea. They contain unique taxa assemblages and play the precious role of refuge for endemic and/or “relict” species. Although the Apulian Adriatic coast, in particular the Gargano and Bari coasts, hosts numerous marine caves, only two caves have been studied for poriferans. In this paper, we present the first data on the sponge fauna of the Colombi Cave, a semi-submerged cave 70 meters long, located along the cliff of Polignano a Mare (Apulian coast). Three stations have been identified at the entrance, in the middle and at the innermost part. A non-destructive photographic method was employed, followed by advanced image analysis and targeted sampling of some species. A total of 55 sponge taxa were identified in the cave. Porifera dominated the benthic community in each station and reached the maximum covering percentage in semi-dark conditions at the innermost station. The present study improves the state of knowledge of Apulian caves and can be used both for comparative studies and as a solid basis for future monitoring.